PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT ASTRA HONDA MOTOR CIKARANG - Dian Sudiantini; Nia Nurfitri; Indah Wulandari; Immanuel Pharosandika Sihombing; Bagus Naufal Putra Shawa (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
The purpose of this research is to learn how the working conditions and morale of the employees at PT Astra Honda Motor Cikarang affect their productivity. Employee output can be boosted by providing a pleasant and motivating workplace. The information and publications used in this study are the sources of the qualitative data. This study's findings corroborate those of others that have found that factors such as office climate and employee motivation have a role in how productively workers get their jobs done. Work motivation can be affected by things like remuneration that is in line with the contract and a pleasant workplace, according to this study. The theory of needs proposed by Abraham Maslow is another tool for gauging employee motivation. Physiological, safety, social, appreciation, and self-actualization demands all fall into this category. The results of this investigation also indicate that the conditions of the workplace have an effect on productivity. This study provides valuable insight into the elements that affect employee performance and may be used as a guide for businesses as they work to manage and enhance staff output.